Behavior of glutamic-pyruvic and glutamic-oxaloacetic transaminase in normal adult subjects - Berendsohn S., Siegfried (1959)
Was conducted to study the behavior of transaminases T.G.P. and T.G.O. in normal adult subjects and the results were subjected to statistical and comparative studies with those by other authors.